Writing rights: suturing Spivak's postcolonial and de Sousa Santos' decolonial thought. Issue 1 (2nd January 2022) - de Jong, Sara
ABSTRACT: Exchange between postcolonial and decolonial thought has been hampered by intellectual and political divisions despite a shared concern with decentring colonial hegemonies. Against the grain, this article brings the work of Boaventura de Sousa Santos into conversation with Gayatri C. Spivak's, centring on one key converging issue of concern – human rights. I argue that both thinkers share what I call a 'reluctant commitment' to a human rights framework, while recognizing its tainted history and current instrumentalization for hegemonic imperial ends. I identify and weave together the strands that form the basis for their reluctant commitment, their critique of human rights, and their proposals for a reconfigured framework of human rights. The article maps how Spivak and de Sousa Santos aim to reconfigure a liberal human rights frame by suturing it to alternative ethical systems, including responsibility-based systems and other conceptions of dignity. It shows common patterns in their work, including their concern that binary global divisions undermine the supposed universality of the human rights framework and the risks of equating law with ethics. Tracing the deconstructive and reconstructive strategies at work in Spivak's and de Sousa Santos' writing helps to break down the walls between decolonial and postcolonial scholarship.